Attitudes Toward Medical Cannabis Legalization Among Serbian Medical Students. (29th July 2017) - Vujcic, Isidora; Pavlovic, Aleksandar; Dubljanin, Eleonora; Maksimovic, Jadranka; Nikolic, Aleksandra; Sipetic-Grujicic, Sandra
ABSTRACT: Background : Currently, medical cannabis polices are experiencing rapid changes, and an increasing number of nations around the world legalize medical cannabis for certain groups of patients, including those in Serbia. Objectives : To determine medical students' attitudes toward medical cannabis legalization and to examine the factors influencing their attitudes. Methods : Fourth-year medical students at the Faculty of Medicine, University of Belgrade, had participated in a cross-sectional study. Data were collected by an anonymous questionnaire. Results : Overall, 63.4% students supported medical cannabis legalization, and only 20.8% supported its legalization for recreational use. Students who previously used marijuana ( p <.001) and alcohol ( p =.004) were significantly more in favor of medical cannabis legalization compared with students who never used them. Support for marijuana recreational use was also related to prior marijuana ( p <.001) and alcohol consumption ( p =.006). Only cancer (90.4%) and chronic pain (74.2%) were correctly reported approved medical indications by more than half the students. Students who supported medical cannabis legalization showed better knowledge about indications, in contrast to opponents for legalization who showed better knowledge about side effects. Beliefs that using medical cannabis is safe and has health benefits were correlated with support for legalization, and previous marijuana and alcohol use, while beliefs that medical cannabis poses health risks correlated most strongly with previous marijuana use. Conclusions/Importance : The medical students' attitudes toward medical cannabis legalization were significantly correlated with previous use of marijuana and alcohol, knowledge about medical indications and side effects, and their beliefs regarding medical cannabis health benefits and risks.